2015
DOI: 10.1007/s12094-015-1347-2
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-197 and miRNA-184 are associated with brain metastasis in EGFR-mutant lung cancers

Abstract: miRNA-197 and miRNA-184 are overexpressed in EGFR-mutant patients with BM and they might be a new biomarker for stratifying the risk of BM in this subpopulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Furthermore, several tumor suppressor genes such as CTNNAI, IKZFI, or EBF3 (Bennett et al, 2008;Ye et al, 2009;Javierre et al, 2011), might become novel targets of miR-197 during EMT induction, of which much work is warranted. Recently, in a retrospective study, J. Remon et al suggested that high-miR-197 might predict the risk of brain metastases information in EGFR-mutant-NSCLC (Remon et al, 2015) and EGFR mutational status represented a better overall survival in NSCLC with brain metastasis (Eichler et al, 2010). As for, the direct nexus of miR-197 and EGFR remains elucidated.…”
Section: Mir-197 In Invasion and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several tumor suppressor genes such as CTNNAI, IKZFI, or EBF3 (Bennett et al, 2008;Ye et al, 2009;Javierre et al, 2011), might become novel targets of miR-197 during EMT induction, of which much work is warranted. Recently, in a retrospective study, J. Remon et al suggested that high-miR-197 might predict the risk of brain metastases information in EGFR-mutant-NSCLC (Remon et al, 2015) and EGFR mutational status represented a better overall survival in NSCLC with brain metastasis (Eichler et al, 2010). As for, the direct nexus of miR-197 and EGFR remains elucidated.…”
Section: Mir-197 In Invasion and Metastasismentioning
confidence: 99%
“…Thus, it was of great concern to investigate the roles and potential mechanisms of key miRNAs in tumorigenic driver pathways. Among them, miR-197, transcribed from the genomic region of chromosome 1p13.3, was found to be significantly dysregulated in a wide range of diseases, such as lung cancer (Remon et al, 2015), breast cancer (Shaker et al, 2015), ovarian cancer (Zou et al, 2015), hepatocellular carcinoma (HCC) , colorectal cancer , thyroid cancer (Weber et al, 2006), head and neck carcinoma (Dai et al, 2011), prostate cancer , follicular thyroid carcinoma (FTC) (Weber et al, 2006), non-alcoholic fatty liver disease (Celikbilek et al, 2014), primary biliary cirrhosis (Ninomiya et al, 2013). Furthermore, increasing evidences had confirmed that miR-197 played a vital role in cell proliferation, apoptosis, differentiation, metastasis and drug resistance, as well as other cellular processes through interacting with particular RNA species (Huang et al, 2014) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate Cox proportional hazard regression analysis of each parameter suggested that high miR-423-5p expression resulted in significantly adverse prognostic factors that were independent of BM. The altered expression of a series of NSCLC-associated miRNAs was identified in previous studies (e.g., miR-675-5p, miR-200, and miR-1253) 22 25 . However, miRNAs associated with the risk of developing BM in NSCLC have not been extensively researched.…”
Section: Discussionmentioning
confidence: 54%
“…The results of the experiments of remon et al revealed three microrNas involved in Nsclc brain metastasis. These are mir-197, mir-184 and mir-423-5p over-expressed in Nsclc Bm+ patients compared to a control group of Nsclc Bm-patients 33 . mirNa-197 overexpression is a potential biomarker for early detection of lung cancers and also correlates with metastasis 34 .…”
Section: The Role Of Mirnas In Brain Metastasismentioning
confidence: 87%